Abu Nasr al-Farabi: The Second Teacher! A Giant in Philosphy, Metaphysics and Teaching Methodology! (872 – 950) - Haque, Anwar Ul (International Journal of Pathology, 2018)
Abu Nasr Mohammad Ibn al-Farakh Farabi agreat philosopher, renowned scholar andalchemist was born in a small village Wasij, nearFarab in Turkistan in 259 A.H. (870 A.D.)